Pengukuran Atribut Psikometrik Tes Literasi Sains Untuk Siswa Madrasah Tsanawiyah - Satria Bungaran; Hafnati Rahmatan; Andi Ulfa Tenri Pada (Postgraduate, University of Mataram, 2025)
The purpose of this research is to measuring the validity and reliability of scientific literacy test instruments. Scientific literacy test instruments are reviewed from theoretical validity (construct, relevance and clarity), empirical validity, and reliability. This research was conducted using a quantitative approach. Data was collected using a questionnaire and tested to measure the eligibility of the test for use in exams. The scientific literacy test instrument tested for theoretical validity through expert judgment involving three validators. The scientific literacy test instrument is considered valid if it has a content validity coefficient value ≥ 0.667. After being declared theoretically valid, the scientific literacy test instrument was then tested on 100 students. The results of the scientific literacy test instrument trials are then analyzed to determine empirical validity and reliability. The results showed that 26 scientific literacy test instruments were declared theoretically valid with each aspect (construction, relevance and clarity) having a content validity coefficient value of ≥ 0.667. The test instrument is declared empirically valid where each question item has rcount > 0.195 (α=0.05 and n=100). The test instrument was declared reliable with a reliability coefficient value of 0.805 > 0.707.